Security Analysis on an Optical Encryption and Authentication Scheme Based on Phase-Truncation and Phase-Retrieval Algorithm - Xiong, Y. (Institute of Electrical and Electronics Engineers Inc., 2021)
10.1109/JPHOT.2019.2936236